Synthesis of new zinc phthalocyanines including schiff base and halogen; photophysical, photochemical, and fluorescence quenching studies - Yuzeroglu, Murat; Karaoglan, Gulnur Keser; Kose, Gulsah Gumrukcu; Erdogmus, Ali (ELSEVIER, 2021)
This study reports a series of new symmetrical tetra substituted zinc phthalocyanines namely {2,9,16,23-Tetra-(4-[4-{[(1E)-(4-fluorophenyl)methylene]amino}phenoxy])-phthalocyaninato} zinc(II) (7), {2,9,16,23-Tetra -(4-[4-{[(1E)-(4-chlorophenyl)methylene]amino}phenoxy])-phthalocyaninato}zinc(II) (8), and {2,9,16,23-Tetra-(4-[4-{[(1E)-(4-bromophenyl)methylene] amino}phenoxy])-phthalocyaninato}zinc(II) (9). The resulting macromolecules were characterized using some spectroscopic methods consisting of UV-Vis, FT-IR, H-1 NMR, and MALDI-TOF MS spectroscopy, together with elemental analysis. The photophysicochemical features of the newly synthesized phthalocyanines includiing fluorescence, photodegradation, and singlet oxygen quantum yields were studied in different solvents such as DMF, DMSO, and THF to explore their potential as suitable photosesitizers. Solvent effect on the photophysical and photochemical parameters of the tetra-substituted phthalocyanines bearing the 4-{[(1E)-(4-fluorophenyl)methylene]amino}phenoxy, 4-{[(1E)-(4-chlorophenyl)methylene]amino}phenoxy, 4-{[(1E)-(4-bromophenyl)methylene]amino}phen-oxy groups were investigated, as well. In comparison to the known Schiff base containing phthalocyanines, the newly synthesized compounds exhibited higher singlet oxygen values. Singlet oxygen yields of the complexes (7-9) were obtained between 0.57 and 0.86. Due to the high singlet oxygen yields of compounds (7-9), they can be listed as photosensitizers in the implementation of photocatalytic applications such as photodynamic therapy (PDT) which is an efficient method for the treatment of cancer. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Zinc (II) phthalocyanine; Schiff base; Halogen; Fluorescence; Photochemistry; Photophysical; PHOTODYNAMIC THERAPY; SUBSTITUTED PHTHALOCYANINES; MECHANISMS; PHOTOSENSITIZERS; SILICON; AGGREGATION; INDIUM(III); DERIVATIVES; MOIETIES; PHENOXY; Chemistry